Mobility control of uranium and other potentially toxic elements in mine waters by ochre-precipitates - Valente, Teresa Maria Fernandes (2019)
Mineral-water interaction in mine drainage often results in the formation of iron-rich precipitates, called ochre products. They often comprise particles in the nanoscale, known by their strong reactivity. The present study focuses on these nanoprecipitates formed in streams that receive water from a U-Ra mine. Water and the ochre-precipitates that cover the streambed were sampled for geochemical and mineralogical characterization. Results indicate low crystallinity and variety of morphology of the ochre product, which is mainly composed by ferrihydrite in coexistence with minor hematite. The work concludes by noting the potential relevance of these nanophases in fate and transport of elements that pose major environmental concern, namely in uranium-rich mine waters.